To solve the equation \(-2(3x - 15) = -56\), follow these steps:
-
Distribute -2 on the left side of the equation: \[ -2 \cdot 3x + 30 = -56 \] This simplifies to: \[ -6x + 30 = -56 \]
-
Next, isolate the term with \(x\) by subtracting 30 from both sides: \[ -6x = -56 - 30 \] Simplifying the right side gives: \[ -6x = -86 \]
-
Now, divide both sides by -6: \[ x = \frac{-86}{-6} \] This simplifies to: \[ x = \frac{86}{6} \] Reducing the fraction: \[ x = \frac{43}{3} \]
Thus, the solution for \(x\) is: \[ \boxed{\frac{43}{3}} \]